Analysis of Safety & Security on Crossings System in IndonesiaSingapore-Malaysia & Thailand’s Borde - Hartanto, Hartanto; Sugiharto, Rudy; Victoria, Ong Argo (IWTJ : International Water Transport Journal, 2020)
As a border on the island of Sumatra, the city of Batam and Natuna sea is the link between Indonesia-Singapore-Malaysia & Thailand. For all of these, safeguards are needed, especially for shipping in the territory of Indonesia, because maritime safety greatly affects sustainable development efforts, especially marine transportation activities. Batam City is included in the Riau Islands province. The Riau Islands Province is located in a very strategic location considering that it is in the border area between countries, neighboring one of the world's business centers (Singapore) and is supported by the existence of an international sea transportation network with busy traffic. In otherside, Kota Bharu and Golok River MalaysiaThailand were included in the crossing system beside the sea transportation in Batam, and South China Sea/Natuna sea. Sea transportation plays a very important role in a maritime country like Indonesia, whose territory is an archipelago. Regarding sea transportation, there are 3 aspects that are interrelated with each other, namely sea traffic and transportation facilities, ports, shipping safety and security. Act No. 17 of 2008 concerning shipping, in its general provisions states that the safety and security of shipping is a condition where safety and security requirements are fulfilled in waters, ports and the maritime environment. Therefore, all parties related to shipping activities must fulfill predetermined requirements. Through concrete steps, compliance with shipping safety and security regulations will create a high level of safety and security. Therefore, it is hoped that the guarantee of safety and security in the field of sea transportation can synergize the pattern of periodic supervision of meeting the safety and security aspects that have been determined.